2007
DOI: 10.1177/230949900701500225
|View full text |Cite
|
Sign up to set email alerts
|

Occult Acetabular Fractures in Elderly Patients: A Report of Three Cases

Abstract: Three elderly patients with acetabular fractures not evident on the initial plain radiographs are presented. All had a fall and were unable to bear weight. Cross-sectional imaging and repeated plain radiography confirmed fractures of the acetabulum. Occult acetabular fractures may occur in elderly patients after a fall and present with persistent discomfort and difficulty walking. When there is reason to suspect such a fracture, further diagnostic studies, including a Judet view radiograph, bone scan, computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Acetabular injuries are followed by polytrauma in 20% -50% of cases. In 36% of cases, acetabular fracture is accompanied with injury of the lower extremities ( 2 ). Classification of acetabular fractures by Judet and Letournel is used as a guide to treatment and as a comparison method regarding the results of other authors.…”
Section: Introductionmentioning
confidence: 99%
“…Acetabular injuries are followed by polytrauma in 20% -50% of cases. In 36% of cases, acetabular fracture is accompanied with injury of the lower extremities ( 2 ). Classification of acetabular fractures by Judet and Letournel is used as a guide to treatment and as a comparison method regarding the results of other authors.…”
Section: Introductionmentioning
confidence: 99%
“…Kakar et al [7] reported three cases of occult acetabular fractures following a fall, identified only after further imaging due to ongoing discomfort and difficulty walking. There was an ipsilateral THA present in one of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[13] were the fractures evident on the initial plain radiographs. All patients had suffered a previous fall and were unable to bear weight.…”
Section: Discussionmentioning
confidence: 99%
“…Such additional studies may include Judet view radiographs, bone scanning, computed tomographic scans or magnetic resonance imaging [13, 14]. In our cases, the x-rays were repeated after the initial mis-diagnosis; no CT-scan was needed as secondary displacement occurred in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation